Normal luminal bacteria, especially Bacteroides species, mediate chronic colitis, gastritis, and arthritis in HLA-B27/human beta2 microglobulin transgenic rats. - Rath, H C; Herfarth, H H; Ikeda, J S; Grenther, W B; Hamm, T E, Jr; Balish, E; Taurog, J D; Hammer, R E; Wilson, K H; Sartor, R B (The Journal of Clinical Investigation, 1996)
Genetic and environmental factors are important in the pathogenesis of clinical and experimental chronic intestinal inflammation. We investigated the influence of normal luminal bacteria and several groups of selected bacterial strains on spontaneous gastrointestinal and systemic inflammation in HLA-B27 transgenic rats. Rats maintained germfree for 3-9 mo were compared with littermates conventionalized with specific pathogen-free bacteria. Subsequently, germfree transgenic rats were colonized with groups of five to eight bacteria that were either facultative or strictly anaerobic. Transgenic germfree rats had no gastroduodenitis, colitis, or arthritis, but developed epididymitis and dermatitis to the same degree as conventionalized rats. Colonic proinflammatory cytokine expression was increased in transgenic conventionalized rats but was undetectable in germfree and nontransgenic rats. Colitis progressively increased over the first 4 wk of bacterial exposure, then plateaued. Only transgenic rats colonized with defined bacterial cocktails which contained Bacteroides spp. had colitis and gastritis. Normal luminal bacteria predictably and uniformly induce chronic colonic, gastric and systemic inflammation in B27 transgenic F344 rats, but all bacterial species do not have equal activities.